Predictors of diabetes distress in patients with type 2 diabetes mellitus - Islam, Mohammad Rashedul; Islam, Mohammad Shafiqul; Karim, Mohammad Rizwanul; Alam, Ummul Khair; Yesmin, Khadiza (International Journal of Research in Medical Sciences, 2017)
Background:Diabetes distress is a condition distinct from depression that is related to diabetes outcomes.This study intends to identify the predicting risk factors of diabetes distress in Bangladeshi type 2 diabetes mellitus patients. Methods:A cross sectional study was conducted from January to June, 2012 in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. Data were collected through interview and reviewing documents. Results:Among 165 respondents, the proportion of diabetes distress was 48.5% (n=80) which include 22.4% (n=37) high distress and 26.1% (n=43) moderate distress. Glycemic status measured by HbA1c was the best predictor of diabetes distress [Adjusted odds ratio (AOR) 1.56; 95% Confidence Interval (CI) 1.16 to 2.10]. Insulin users were five times more likely to develop distress [Adjusted odds ratio (AOR) 5.05; 95% Confidence Interval (CI) 1.20 to 21.19] than users of oral anti-diabetic agents. Other predictors of diabetes distress were duration of DM [Adjusted odds ratio (AOR) 1.27; 95% Confidence Interval (CI) 1.06 to 1.52], Diabetic complications [Adjusted odds ratio (AOR) 3.92; 95% Confidence Interval (CI) 1.09 to 14.19], Average monthly family income [Adjusted odds ratio (AOR) 1.00; 95% Confidence Interval (CI) 1.00 to 1.00]. Conclusion:HbA1c, treatment modalities, duration of DM, diabetic complications and average monthly family income appeared to be significant predicting factors of diabetes distress among the type 2 diabetes mellitus patients. This should be taken into consideration for effective management of patient.